The expanding role of cytopathology in the diagnosis of HPV‐related squamous cell carcinoma of the head and neck. Issue 1 (8th June 2013) - Holmes, Brittany J.; Westra, William H.; Pantanowitz, Liron
<x xml:space="preserve">Abstract</x> Confirmation of human papillomavirus (HPV) as a causative agent for a subset of biologically and clinically distinct squamous cell carcinomas of the head and neck (HNSCC) has resulted in a growing need and expectation for HPV testing of head and neck cancers. At the same time, opportunities to obtain tissue samples for HPV testing are diminishing: The sensitivity of HPV‐related HNSCC to chemotherapy and ionizing radiation has limited the role of surgical resection, and diagnostic tissue biopsies/resections may not be available in a substantial portion of patients with small or occult primaries. Into this quandary steps the cytopathologist. Fine needle aspirates of metastatic HNSCCs and brushes of oropharyngeal cancers provide a valuable substrate for HPV analysis. These cytologic specimens are suitable for standard tissue‐based methods of HPV detection such as immunoperoxidase and in situ hybridization, but the expanding demands for biomarker analysis of these limited samples is driving the development of alternative assays that eliminate the requirement for high cellularity and complex specimen processing. Various liquid phase assays already in widespread use for HPV analysis of cervical cancer risk may be directly transferrable to the head and neck context. Implementation of these assays may abrogate the current need for tissue acquisition of HNSCCs via a more aggressive surgical procedure. Diagn. Cytopathol. 2014;42:85–93. © 2013 Wiley Periodicals, Inc.